EVALUASI KEBIJAKAN PEMBERDAYAAN MASYARAKAT NELAYAN DI KECAMATAN TINAMBUNG KABUPATEN POLEWALI MANDAR - Manaf, Cicci Yuliah (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The program for the procurement of nylon gill net fishing gear is a form ofactivity carried out by the government in order to empower fishingcommunities in villages that are considered not yet prosperous. KaramaVillage and Tangnga- Tangnga Village are two coastal villages in TinambungSub-district that have been touched by the program for the procurement ofnylon-nylon fishing gear. This study aims to find a program for theprocurement of gill net fishing gear to empower fishermen in TinambungDistrict. The writing of empowerment evaluation theory by Howlet andRamesh is looking at the efforts made by the government, how the output of theefforts made, how the output evaluation with the objectives to be achieved, the effectiveness of the program, and the process of program formation. Theresearch method used is qualitative research. Data collection techniques usinginterviews, observation and documentation. The results of the study indicatethat the government's implementation of the nylon gill net fishing gearprocurement program has been running optimally. However, due to the limitedbudget, only fishermen who pass the lever get assistance.